2004
DOI: 10.1002/syn.20027
|View full text |Cite
|
Sign up to set email alerts
|

Novel peripheral benzodiazepine receptor ligand [11C]DAA1106 for PET: An imaging tool for glial cells in the brain

Abstract: Peripheral benzodiazepine receptor (PBR) is expressed in most organs and its expression is reported to be increased in activated microglia in the brain. [(11)C]PK11195 has been widely used for the in vivo imaging of PBRs, but its signal in the brain was not high enough for stable quantitative analysis. We synthesized a novel positron emission tomography (PET) ligand, [(11)C]DAA1106, for PBR and investigated its in vivo properties in rat and monkey brain. High uptake of [(11)C]DAA1106 was observed in the olfact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
125
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(139 citation statements)
references
References 53 publications
14
125
0
Order By: Relevance
“…We considered two possibilities: adequacy of blockade by DAA1106 and effect of DAA1106 on plasma free fraction. First, Maeda et al (2004) reported that 1 mg/kg DAA1106 caused ∼ 80% occupancy of PBRs in monkey brain, and we used a preblocking dose of 3 mg/kg. Thus, our dose may not have saturated all receptors, which would have caused an overestimation of nonspecific binding and an underestimation of specific binding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We considered two possibilities: adequacy of blockade by DAA1106 and effect of DAA1106 on plasma free fraction. First, Maeda et al (2004) reported that 1 mg/kg DAA1106 caused ∼ 80% occupancy of PBRs in monkey brain, and we used a preblocking dose of 3 mg/kg. Thus, our dose may not have saturated all receptors, which would have caused an overestimation of nonspecific binding and an underestimation of specific binding.…”
Section: Discussionmentioning
confidence: 99%
“…Among this class of ligands, [ 11 C]DAA1106 and [ 18 F]FEDAA1106 ( Fig. 1) have successfully imaged PBRs in human and nonhuman primates with high brain uptake and a high percentage of specific binding (Fujimura et al, 2006;Ikoma et al, 2007;Maeda et al, 2004;Zhang et al, 2003). We also synthesized aryloxyanilide-based PET ligands that have high affinity and selectivity for PBRs: [ 11 C]PBR01, [ 18 F]PBR06, and [ 11 C]PBR28 ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…To ascertain that no relevant studies were omitted from this meta-analysis, we performed a systematic literature search on PubMed. Only articles published after 2004 were included in the search, corresponding to the year when the first report on a second-generation TSPO radioligand was published (33). Search terms included (among others) "psychotic disorder," "schizophrenia," "positron emission tomography," "translocator protein 18 kDa," and "peripheral benzodiazepine receptor" (for the full list of search terms, see the Supplement).…”
Section: Selection Criteria and Search Strategymentioning
confidence: 99%
“…Recently, several other compounds have been evaluated: [ 11 65 Maeda et al, 66 Zhang et al, 67,68 and Fujimara et al 69 have extensively described [ 11 C]DAA1106 and fluorinated derivatives in ex vivo binding experiments on rat brain sections and biodistribution studies in mice. PET imaging has also been performed in normal monkeys or healthy patients, but so far no published data from in vivo experiments using DAA1106 and derivatives in disease states have been published.…”
Section: New Pbr Ligands For Pet Studies Of Microglial Activationmentioning
confidence: 99%